Pemberdayaan kelompok masyarakat sadar wisata (pokdarwis) bina remaja Desa Kunjir terhadap literasi ekonomi digital - Lusmeilia Afriani; Amril Maruf Siregar (Jurnal Sumbangsih, 2022)
The Tourism Conscious Community Group (Pokdarwis) Bina Remaja Kunjir Village is one of the community groups assisted by LPPM Universitas Lampung. This group is part of a group of communities victims of the Sunda Strait Tsunami disaster that occurred at the end of 2018. Efforts to improve infrastructure, socio-economic and have been implemented in order to accelerate the economic revival of the community. One of the main potentials of Kunjir Village is tourism and creative economy. In the previous year, the capacity building activities of the Kunjir Village community in the field of processing handicrafts and village products have been running well. This activity is a follow-up to the previous activity where the service team will continue the wishes of the community by strengthening the ability. Understand, manage, and use technology wisely to be useful in everyday life. Digital literacy not only includes the ability to find and read information from digital media, but also requires a critical thinking process to manage, evaluate and utilize information obtained from various digital sources correctly, carefully, ethically and responsibly. The form of implementation of activities that will be carried out is in the form of training and technical guidance to Pokdarwis with the scope of skill enrichment in the field of digitizing handicraft products and promoting tourist attractions. The results of the implementation of the activity will be evaluated so that the benefits of this activity can be felt by the community